Structural, ion transport parameter and electrochemical properties of plasticized polymer composite electrolyte based on PVA: a novel approach to fabricate high performance EDLC devices - Brza, Mohamad A.; Aziz, Shujahadeen; Anuar, Hazleen; Ali, Fathilah (Elsevier Ltd, 2020)
In this study a novel polymer composite electrolytes (PCEs) based on poly (vinyl alcohol) (PVA): Ce(III)-complex:NH4SCN plasticized with glycerol are prepared by solution cast technique. XRD and FTIR routes are used to study the film structure. The crystalline and amorphous areas are determined through the deconvolution of XRD spectra and their values were used to calculate the degree of crstallinity. The deconvolutions of the FTIR of asymmetric C≡N stretching mode are carried out to establish the bands coupled with free ions, contact ion pairs and ion aggregates. The maximum ambient temperature DC conductivity of 2.07 × 10-3 S cm-1 is recorded for the sample with the lowest degree of crystallinity. It was found that the number density (n), mobility (μ) and diffusion coefficient (D) of ions are increased with the glycerol concentration. Field emission scanning electron microscopy (FESEM) is used to examine the effect of plasticizer on film morphology. The DC conductivity trend is interpreted in detail with the help of dielectric properties. It is found that the transference numbers of ions (tion) and electrons (tel) are 0.965 and 0.035, respectively. It is shown by the linear sweep voltammetry (LSV) that the potential window of the PCE is 2.1V. A shape, which is nearly rectangular at lower scan rates, is identified from cyclic voltammetry (CV). Specific capacitance and energy density are exhibited by EDLC with average of 161.5 F/g and 18.17 Wh/kg, respectively within 400 cycles. The initial power density is shown by EDLC to be 2.825 x 103 W/Kg.